Highly thermally conductive and mechanically robust polyamide/graphite nanoplatelet composites via mechanochemical bonding techniques with plasma treatment. (26th May 2018) - You, Jiwan; Choi, Han-Hyeong; Cho, Jaehyun; Son, Jeong Gon; Park, Min; Lee, Sang-Soo; Park, Jong Hyuk
Abstract: Heat sinks made from polymer/nanocarbon composites have great potential due to their excellent processability, light weight, and low production cost compared to metal heat sinks. However, the thermal conductivity and mechanical properties of conventional polymer/nanocarbon composites have been considered insufficient for practical use as heat sinks. Here, significant improvements in both the thermal conductivity and the mechanical properties of polymer/nanocarbon composites have been achieved by a facile approach, using mechanochemical bonding techniques with plasma treatment (MBP process). Polyamide 66 (PA66) and graphite nanoplatelets (GNPs) are compounded via the MBP process, which can enhance the interfacial affinity between PA66 and GNP and promote the uniform dispersion of GNPs in the composites. The resulting PA66/GNP composites exhibit greatly improved thermal conductivity and mechanical properties. In particular, the thermal conductivity and tensile strength of the composite containing 10 wt% GNPs are over 3 times and 2 times higher than those of the composite prepared via conventional processes, respectively. Moreover, in heating and cooling tests, excellent heat transfer and dissipation properties are observed in the MBP-processed composites, demonstrating their practical applicability as effective heat sinks. Thus, this approach can encourage the development of high-performance, low-cost heat sinks. Graphical abstract: Image 1